Radial Evolution of Interplanetary Shock Properties with Heliospheric Distance: Observations from Parker Solar Probe - Oksana Kruparova; Adam Szabo; Lan K. Jian; František Němec; Jana Šafránková; Zdeněk Němeček; Jacob Pasanen; Ayris Narock; Vratislav Krupar (The Astrophysical Journal Letters)
We present a comprehensive analysis of 66 interplanetary shocks observed by the Parker Solar Probe between 2018 November and 2024 January. Among these, 33 events fulfilled the Rankine–Hugoniot (R-H) conditions, ensuring reliable asymptotic plasma parameter solutions. The remaining 33 events could not be confirmed by the standard R-H approach—potentially including wave-like structures—yet were analyzed via averaging and mixed-data methods to obtain robust shock parameters. Utilizing our ShOck Detection Algorithm database, the shocks are categorized into fast-forward, fast-reverse, slow-forward, and slow-reverse types. We investigate the statistical properties of these shocks, focusing on correlations between key parameters—magnetic field compression, density compression, shock normal angle, and change in velocity—and heliocentric distance. Significant positive correlations are identified between heliocentric distance and both magnetic field compression and density compression, suggesting that shocks strengthen as they propagate away from the Sun, largely due to the high local magnetosonic speeds closer to the Sun that can suppress shock formation except in extremely fast events. These findings provide new insights into the dynamic processes governing shock evolution in the inner heliosphere, including scenarios where the near-radial magnetic field geometry may lead to predominantly quasi-parallel shock configurations and thus affect near-Sun particle acceleration efficiency. We also provide strong evidence for the existence of slow-mode shocks near the Sun, contributing to the understanding of shock formation and evolution in the inner heliosphere.